2021
DOI: 10.1371/journal.pone.0252158
|View full text |Cite
|
Sign up to set email alerts
|

Time in blood glucose range 70 to 180 mg/dL and survival rate in critically ill patients: A retrospective cohort study

Abstract: Background While time in targeted blood glucose range (TIR) 70–140 mg/dL is a known factor associated with mortality in critically ill patients, it remains unclear whether TIR is associated with 28-day mortality under the glycemic control with a less tight target glucose range of 70–180 mg/dL. We aimed to examine whether TIR 70–180 mg/dL was associated with 28-day mortality. Methods This is a retrospective cohort study using data from a tertiary care center in Japan collected from January 2016 through Octobe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…One of our findings was that the TIR of absolute normoglycemia (70–140 mg/dL) was significantly associated with in-hospital mortality only among patients with A1C < 6.5% but not among those with A1C ≥ 6.5%, which was consistent with previous studies investigating a time in targeted blood glucose range of 70–139 mg/dL 13 or a time in blood glucose range using the more liberal upper limit (180 mg/dL) 14 . Therefore, our results reaffirm that the range of 70–140 mg/dL cannot be a target for all patients, as well as the importance of individual blood glucose targets in accordance with A1C levels.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…One of our findings was that the TIR of absolute normoglycemia (70–140 mg/dL) was significantly associated with in-hospital mortality only among patients with A1C < 6.5% but not among those with A1C ≥ 6.5%, which was consistent with previous studies investigating a time in targeted blood glucose range of 70–139 mg/dL 13 or a time in blood glucose range using the more liberal upper limit (180 mg/dL) 14 . Therefore, our results reaffirm that the range of 70–140 mg/dL cannot be a target for all patients, as well as the importance of individual blood glucose targets in accordance with A1C levels.…”
Section: Discussionsupporting
confidence: 92%
“…Third, we did not consider the presence or absence of diabetes. However, previous studies have shown that A1C has a stronger effect on the relationship between glucose measurements and outcomes than diabetes 13 , 14 . Fourth, we defined relative normoglycemia as measured blood glucose levels in the range of 70–140% of ADAG based on previous studies; however, the external validity of this range has not yet been assessed.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations